conomic crises in the period of conflict between AL-Amin and AL-Mamun (193- 218 AH = 809- 833 CE (Journal of the College of Basic Education, 2022)
The research deals with a historical study of the economic crises during the conflict between the Abbasid Caliph Al-Amin and his brotherhood and his Crown Prince Al-Mamoun, and the importance of the research is evident through its review of the political conflicts and their impact on the administrative and economic conditions of the Arab Islamic state. And the change in the administrative and monetary system of the state’s regions in the Abbasid era, and the subsequent break in power, which cost the caliphate’s budget a great deal of sending a well-equipped military campaign from the Abbasid Caliphate’s center on the one hand, and the eastern regions represented by Khorasan and what follows that which are under the authority and administration Al-Ma'mun, on the other hand, and during the period of the conflict, which lasted for five years (193-198), military and civil rebellions emerged against the policy of the two caliphs who were trustworthy, and after him, the safe, which cost the state treasury a lot ... as corruption and security instability prevailed during that period, theft, robbery, and public exploitation increased dramatically. Trade and markets were ruined, and prices rose ... until the caliphate of Al-Mamun stabilized and his return to Baghdad... which worked to restore security and political and economic stability to the country ..